2013
DOI: 10.2224/sbp.2013.41.6.939
|View full text |Cite
|
Sign up to set email alerts
|

The effects of a food project on children's categorization skills

Abstract: I conducted this study to investigate the effects of project-based education on children's categorization skills. I used an experimental design with the pre and posttest control group. Participants were 47 6-year-old children who attended a public preschool. Children in the experimental group completed a "Food Project", which continued for 12 weeks. The children in the control group undertook the regular preschool program. Data about the children's categorization skills were obtained by using the Categorizati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…Finally, on request of an anonymous reviewer, we added two extra studies included in a meta-analysis. Therefore, the final sample of articles reviewed for inclusion comprised eleven articles (see Table 1) [37][38][39][40][41][42][43][44][45][46][47]. Fig 1 shows a PRISMA flowchart summarizing the literature search process.…”
Section: Plos Onementioning
confidence: 99%
See 1 more Smart Citation
“…Finally, on request of an anonymous reviewer, we added two extra studies included in a meta-analysis. Therefore, the final sample of articles reviewed for inclusion comprised eleven articles (see Table 1) [37][38][39][40][41][42][43][44][45][46][47]. Fig 1 shows a PRISMA flowchart summarizing the literature search process.…”
Section: Plos Onementioning
confidence: 99%
“…this review obtained positive results regarding the impact of PjBL in academic achievement of students immediately after the intervention [36,38,41,42,46,47] or in the long term [44]. Among the rest, two studies did not find significant differences between the experimental and control groups [37,43], one study did not report any quantitative data [40], and another one offered no comparison between the experimental and control groups [39]. In addition, the studies showed considerable heterogeneity in terms of participants' age (from preschoolers to 11 years old students), duration of the intervention (ranging from 3 to 32 weeks), and measured outcomes (e.g., categorization skills or English knowledge).…”
Section: Plos Onementioning
confidence: 99%
“…The mathematical competencies of primary-school aged children differ from each other at the beginning of the school (Aslan, 2020;Burchinal, McCartney, Steinberg, Crosnoe, Friedman, McLoyd & Pianta, 2011;Sarama & Clements, 2009). Children with low SES have less mathematical knowledge than their peers (Aslan, 2013;Klibanoff, Levine, Huttenlocher, Vasilyeva & Hedges, 2006). It is argued that the disadvantage of children with lower SES in terms of math knowledge is due to the quality of the support parents provide to their children at home (DeFlorio & Beliakoff, 2015;Melhuish et al, 2008).…”
Section: Introductionmentioning
confidence: 99%